TRAUMA MASA LALU DAN MEKANISME PENGENDALIAN DIRI TOKOH KARANG DALAM NOVEL AKU TAK MEMBENCI HUJAN: PENDEKATAN PSIKOANALISIS - Lihatu Soliha; Elsa Mulya Karlina (CV. Adiba Aisha Amira, 2025)
Hiis research aims to describe the form of past trauma experienced by Karang's character in the novel Aku Tak Membenci Hujan by Sri Puji Hartini and to describe the self-control mechanism displayed by Karang's character in the novel Aku Tak Membenci Hujan by Sri Puji Hartini. The problems described in this study are how the form of past trauma experienced by the character Karang in the novel Aku Tak Membenci Hujan by Sri Puji Hartini, and how the self-control mechanism displayed by the character Karang in the novel Aku Tak Membenci Hujan by Sri Puji Hartini. The research method used is a qualitative approach with library research. The results of this study show that the main character, Karang, in the novel Aku Tak Membenci Hujan by Sri Puji Hartini, experienced a very complex past trauma, namely physical trauma, psychological trauma, environmental or situational trauma. This trauma was experienced from her childhood until she was a teenager. The trauma resulted in dissociative identity or multiple personality as a form of self-control mechanism, namely id, ego, and super ego.